Selective interspecific information use in the nest choice of solitary bees - Loukola, Olli J; Gatto, Elia; Híjar-Islas, Ana C; Chittka, Lars (Animal biology (Leiden, Netherlands), 2020)
Abstract Most of the studies on learning in bees have focused on the foraging context; we know little about the preferences and cognitive processes in nest-site selection, especially in solitary bees. The majority of the bee species are solitary and in contrast to eusocial bees, solitary bees’ cognition and social information use have remained largely unstudied. Solitary cavity-nesting mason bees (Osmia spp.) are an ideal system to study interspecific information use in nest choice in the wild as many species share similar nesting requirements. Here, we show that the blue mason bee (O. caerulescens) and the orange-vented mason bee (O. leaiana) examine hallmarks of parasitization of the nests of red mason bees (O. bicornis) before deciding where to establish their own nests. They were also presented with contextual cues (geometric symbols) that could be linked to parasitization by observational learning. Subjects subsequently had the choice of nesting in a nest site marked by the symbol that matched, or did not match, the one seen at the parasitized or healthy nest. We show that the bees copied and rejected the symbol of the examined nest manipulated to exhibit successful and unsuccessful nesting, respectively. We conclude that solitary bees use interspecific information in their nest-site selection. In contrast with current theories of species coexistence, niche overlap between species may dynamically change depending on the observed success of surrounding individuals.